War and displacement in the twentieth century
1 online resource (vi, 277 pages)
Keywords: "Human displacement has always been a consequence of war, written into the myths and histories of centuries of warfare. However, the global conflicts of the twentieth century brought displacement to civilizations on an unprecedented scale, as the two World Wars shifted participants around the globe. Although driven by political disputes between European powers, the consequences of Empire ensured that Europe could not contain them. Soldiers traversed continents, and civilians often followed them, or found themselves living in territories ruled by unexpected invaders. Both wars saw fighting in Europe, Africa, the Middle East and the Far East, and few nations remained neutral. Both wars saw the mass upheaval of civilian populations as a consequence of the fighting. Displacements were geographical, cultural, and psychological; they were based on nationality, sex/gender or age. They produced an astonishing range of human experience, recorded by the participants in different ways. This book brings together a collection of inter-disciplinary works by scholars who are currently producing some of the most innovative and influential work on the subject of displacement in war, in order to share their knowledge and interpretations of historical and literary sources. The collection unites historians and literary scholars in addressing the issues of war and displacement from multiple angles. Contributors draw on a wealth of primary source materials and resources including archives from across the world, military records, medical records, films, memoirs, diaries and letters, both published and private, and fictional interpretations of experience"--